Analisis Transaparansi Manajerial pada Perusahaan Transportasi Tambang (Studi Kasus: PT Surya Saputra Sentosa) - A. Musyarrafah Vetriyani; Anshar (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the implementation of managerial transparency in a mining transportation company, focusing on a case study of PT Surya Saputra Sentosa, operating in the nickel mining area of Southeast Sulawesi, Indonesia. Managerial transparency is one of the key pillars in the application of good corporate governance, especially in the mining sector, which is characterized by complex and high-risk operations. This research employs a qualitative method using a case study approach. Data were collected through in-depth interviews, document analysis, and limited observations of reporting flows and managerial decision-making processes. The findings reveal that transparency practices at PT Surya Saputra Sentosa remain partial and lack formal structure. The company faces several challenges, including the absence of technology-based reporting systems, dominance of informal communication, and limited managerial understanding of good corporate governance principles. Nevertheless, there are initial efforts by management to improve reporting systems and clarify roles and responsibilities. This study offers practical insights for developing a more adaptive transparency system in medium-scale mining transportation companies.